PENINGKATAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL INTERAKSI SOSIAL DI KELAS 4 SD NEGERI NO. 100619 JANJIMANAON KECAMATAN BATANG ANGKOLA KABUPATEN TAPANULI SELATAN - Tanjung, Rodiah (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
The purpose of this study is to describe the improvement of student learning outcomes in social studies learning using the social interaction model in grade IV of SD N0. 100619 Janjimanaon, Batang Angkola District, South Tapanuli District. This research is a Classroom Action Research (PTK) carried out at SD N0. 100619 Janjimanaon, Batang Angkola District, South Tapanuli District. The subjects of this study are classroom teachers and students totaling 22 students. Consisting of 10 male students and 12 female students. The approach used in this study is a quantitative and qualitative approach, the research is carried out in 2 cycles. Cycle I consists of two meetings and cycle II consists of one meeting. The research procedure consists of four stages, namely Planning, Implementation, Observation and Reflection. The results of the study showed an increase from pre-cycle to cycle I and from cycle I to cycle II. The completeness of students before treatment reached (22.73%), while in cycle 1 after treatment, the completeness of students reached (36.36%), and in cycle II the completeness of students increased to (81.82%). Based on these results, it can be concluded that using the social interaction model can improve student learning outcomes in social studies learning in grade IV.